2018
DOI: 10.1111/pedi.12768
|View full text |Cite
|
Sign up to set email alerts
|

Association between 14 bp insertion/deletion HLA‐G functional polymorphism and insulin resistance in a cohort of Italian children with obesity

Abstract: We showed a strong association between HLA-G 14 bp ins/ins genotype and HOMA in obese children and adolescents. This association could be hypothetically modulated by subclinical inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…At the same time, the expression level of nonclassical HLA-class I molecule G (HLA-G) is downregulated in childhood obesity and in obese adolescents with insulin resistance these changes were more significant. Recently, it was shown that there is a strong association between HLA-G 14 bp ins/ins genotype and insulin resistance in obese children and adolescents (Marzuillo et al 2018), but at the same time, there were identified two opposite sides of HLA-G function: beneficial to be promoted or deleterious to be blocked (Amiot et al 2015;Carosella et al 2015). Thus, additional studies may be necessary to determine the functional significance of HLA-G gene expression in obese subjects both with and without insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the expression level of nonclassical HLA-class I molecule G (HLA-G) is downregulated in childhood obesity and in obese adolescents with insulin resistance these changes were more significant. Recently, it was shown that there is a strong association between HLA-G 14 bp ins/ins genotype and insulin resistance in obese children and adolescents (Marzuillo et al 2018), but at the same time, there were identified two opposite sides of HLA-G function: beneficial to be promoted or deleterious to be blocked (Amiot et al 2015;Carosella et al 2015). Thus, additional studies may be necessary to determine the functional significance of HLA-G gene expression in obese subjects both with and without insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dual role of HLA-G in solid and liquid tumors was shown: HLA-G inhibits the proliferation of malignant B cells due to the interaction between HLA-G and its receptor ILT2, which mediates negative signaling on B cell proliferation (Rouas-Freiss et al 2014). Recently, it was shown that there is a strong association between HLA-G 14 bp ins/ins genotype and insulin resistance (evaluated by homeostasis model assessment [HOMA]) in obese children and adolescents (Marzuillo et al 2018).…”
mentioning
confidence: 99%
“…For the first time in the literature, Ozer Oztekin who is an author of the present study hypothesized that HLA‐G may possibly be involved in the development of GDM 18 . Thereafter, HLA‐G is shown to be associated with insulin resistance, Type 2 DM and GDM by several studies 19–21 . Previously, we have also shown an association between HLA‐G and polycystic ovarian syndrome (PCOS), which is a disease associated with insulin resistance 22 …”
Section: Introductionmentioning
confidence: 51%
“…In inflammatory myopathy, CD8 T cells destroy non-necrotic muscle fibers, showing a response mediated by HLA class I restricted cytotoxic T cells against surface antigens expressed in muscle fibers. Marzuillo et al [ 30 ] reported that muscle fibers, in an inflamed environment, co-express HLA-G, raising the intriguing possibility that HLA-G protects muscle fibers from injury mediated by NK cells [ 31 , 32 ]. Locally accumulated inflammatory cells produce a multitude of pro-inflammatory cytokines, including TNF-alpha and IFN-gamma.…”
Section: Discussionmentioning
confidence: 99%